Sex-Specific Difference in Adipose Tissue and Blood Pressure in a New Mouse Model Expressing Human Soluble Prorenin Receptor in Adipocytes. (29th May 2020) - Nichols, Kellea; Poupeau, Audrey; Gatineau, Eva; Arthur, Gertrude; Gong, Ming; Lindner, Volkhard; Yiannikouris, Frederique
Abstract: Objectives: Sex differences exist in obesity associated with cardiovascular disease; however, underlying mechanisms are not completely understood. Previous studies from our laboratory demonstrated that the prorenin receptor (PRR) and its soluble form (sPRR) contribute to adipogenesis and blood pressure control. The present study aimed to determine whether adipose-sPRR stimulated obesity is associated with hypertension and whether it is sex-dependent. Methods: Transgenic mice on the C57BL/6 J background were generated expressing the human form of the soluble prorenin receptor (HsPRR) in a Cre-inducible manner. Male mice expressing Cre recombinase under the control of the adiponectin promotor were bred to heterozygote HsPRR/+ female mice to generate mice over-secreting sPRR (adi-HsPRR) and control littermate mice (CTL). The secretion of sPRR in the media doubled in primary adipocytes of adi-HsPRR mice compared to control mice (sPRR. CTL: 3729 ± 805 pg/ml; adi-HsPRR: 6170 ± 1237 pg/ml, P  < 0.05) validating the mouse model. Male (CTL = 4; adi-HsPRR = 8) and female mice (CTL = 10; adi-HsPRR = 10) were fed a low-fat (LF) diet or a high-fat diet (HF) for 20 weeks. Body weight was assessed weekly and EchoMRI was examined monthly. Results: After 20 weeks on LF diet, adi-HsPRR male mice gained significantly more weight than CTL male mice (CTL: 25.1 ± 0.8 g; adi-HsPRR: 29.0 ± 0.8 g P  < 0.05), whereas no significant differences in body weights were observed in female mice. The body composition revealed a significant increase of fat mass, specifically in the epidydimal fat (CTL: 0.35 ± 0.04 g; adi-HsPRR: 0.61 ± 0.07 g, P  < 0.05), and lean mass of HsPRR male mice compared to CTL male mice. In contrast, female mice exhibited similar body weights (CTL: 20.6 ± 0.3 g; adi-HsPRR: 20.4 ± 0.4 g) and there was no differences of fat mass or lean mass between CTL and adi-HsPRR female mice. The sex-specific mechanism of sPRR on adipogenesis and blood pressure (by radiotelemetry) with LF and HF diet is currently under investigation. Conclusions: Overall, sPRR stimulated body weight gain and fat mass expansion in male mice but not in female mice suggesting that female mice are protected from sPRR induced-hypertrophic effect. Funding Sources: R01_HL142969–01 Yiannikouris, PI 07/15/2018–06/30/2022 NIH/NHLBI Title: The role of soluble prorenin receptor in hypertension associated with obesity Role: Ph.D Graduate Student.